2009
DOI: 10.1128/aem.01386-09
|View full text |Cite
|
Sign up to set email alerts
|

Cryptosporidium spp. in Wild, Laboratory, and Pet Rodents in China: Prevalence and Molecular Characterization

Abstract: To understand the prevalence of Cryptosporidium infection in rodents in China and to assess the potential role of rodents as a source for human cryptosporidiosis, 723 specimens from 18 rodent species were collected from four provinces of China and examined between August 2007 and December 2008 by microscopy after using Sheather's sugar flotation and modified acid-fast staining. Cryptosporidium oocysts were detected in 83 specimens, with an overall prevalence of 11.5%. Phodopus sungorus, Phodopus campbelli, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
114
4
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 121 publications
(131 citation statements)
references
References 52 publications
10
114
4
3
Order By: Relevance
“…in pet rodents (3-6). Also, A. tetraptera and H. nana were observed in rodents of pet shops (3)(4)(5). In our study, the parasitic infections were found at a similar rate (54.9%-57.5%) in hamsters and rabbits.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…in pet rodents (3-6). Also, A. tetraptera and H. nana were observed in rodents of pet shops (3)(4)(5). In our study, the parasitic infections were found at a similar rate (54.9%-57.5%) in hamsters and rabbits.…”
Section: Discussionsupporting
confidence: 68%
“…Also, this tapeworm has been reported in some pet shop rodents (3)(4)(5). Humans have been considered to be susceptible to H. nana (1).…”
Section: Discussionmentioning
confidence: 99%
“…The black rat (Rattus rattus), which originated in tropical mainland Asia and, later spreading to Europe and the rest of the world (Musser and Carleton, 1993), is now found throughout much of coastal Australia including urban and peri-urban habitats (West, 2008). Rodents, which are abundant and widespread, have been considered reservoirs of cryptosporidiosis in humans and farm animals (Lv et al 2009). Nearly 40 rodent species belonging to 11 families (Sciuridae, Muridae, Cricetidae, Castoridae, Geomyidae, Hystricidae, Erethizontidae, Myocastoridae, Caviidae, Hydrochoeridae, and Chinchillidae) have been reported as hosts of Cryptosporidium spp.…”
Section: Rodentsmentioning
confidence: 99%
“…The only exception is a recent study in Egypt, in which it was shown that 23 of 24 of C. parvuminfected preweaned dairy calves had excreted IIdA20G1 (3). In China, 10 C. parvum isolates from pet Siberian chipmunks and hamsters in Henan were identified as IIdA15G1 (22). Despite its rare occurrence in dairy cattle, the IId subtype family is common in humans in the Middle East (14,37), and has also been reported in a few human cases in Portugal, Ireland, the United Kingdom, Belgium, the Netherlands, and Australia (44).…”
mentioning
confidence: 99%